Cyberaggression: The effect of parental monitoring on bystander roles - Levy, Michal; Sela-Shayovitz, Revital (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2020)
The digital world has created new opportunities for aggression through cyberaggression. Despite growing research interest in cyberaggression, little is known about the various bystander roles in the digital interaction. This paper examines the effect of parental monitoring practices (parental restriction, youth disclosure, and parental solicitation) on five bystander roles: aggressor-supporter, defender, help-seeker, outsider, and passive bystander. Data were derived from self-report questionnaires answered by a sample of 501 adolescents in Israel. The findings indicate that adolescents who share their experiences of cyberaggression with their parents are more likely than others to defend the cybervictim. Interaction effects were found between adolescent gender, installing warning applications, parent gender, and the aggressor-supporter role. Boys whose parents installed warning applications and whose fathers monitored their online activities were positively associated with the aggressor-supporter role, while girls who were higher aggressor-supporter reported that their parents used warning applications but did not monitor their online activities. The discussion focuses on the theoretical and practical implications of the effectiveness of parental monitoring on the cyberaggression bystander’s role.